Penerapan Komunikasi Interpersonal Karyawan Terhadap Para Tamu Dalam Mewujudkan Kepuasan Pelayanan Di Caffe Locca Hostel Sanur Bali - Kotaniartha, I Wayan; Bu'u, Christianus Fernando (Dwijendra University, 2022)
Communication is an essential thing in life. Concerning on social interactions formed in society; the right realm to be studied in communication science is interpersonal communication. Further concern at the existence and benefits of interpersonal communication in social life, it will be interesting on the implementation of interpersonal communication within accommodation business in Bali. In the study entitled “Implementation of Employee’s Interpersonal Communication to Guests in Achieving Service Satisfaction at Caffe Locca Hostel Sanur Bali’, the researcher implemented a qualitative approach with all employees of Caffe Locca Hostel Sanur Bali as the subject of the research. The employees, as agents of social interaction to guests, are given the freedom to build interpersonal communication. It can achieve service satisfaction reflected in the online reviews of guests on the Booking.com application. The data were collected by interview, observation, and documentation techniques. Based on the results of analysis, it shows that implementation of employee’s interpersonal communication to guests has employed well enough in accordance to five indicators of interpersonal communication, namely; openness, empathy, support, sense of positivity, as well as equality and equality. It could achieve guests’ service satisfaction reflected in the large number of positive reviews in the last two years, 2018 and 2019